Automated Systems with Fluorescence Detection for Metal Determination: A Review - Arina Skok; Natalia Manousi; Aristidis Anthemidis; Yaroslav Bazel (Molecules)
Industrialization has led to environmental pollution with various hazardous chemicals including pollution with metals. In this regard, the development of highly efficient analytical methods for their determination has received considerable attention to ensure public safety. Currently, scientists are paying more and more attention to the automation of analytical methods, since it permits fast, accurate, and sensitive analysis with minimal exposure of analysts to hazardous substances. This review discusses the automated methods with fluorescent detection developed for metal determination since 2000. It is evident that flow-injection analysis (FIA) with no preconcentration or with solid-phase preconcentration are predominant compared to liquid-phase preconcentration systems. FIA systems are also more widespread than sequential injection analysis (SIA) systems. Moreover, a significant number of works have been devoted to chromatography-based methods. Atomic fluorescence detectors significantly prevail over molecular fluorescence detectors. It must be highlighted that most of the methods result in good figures of merit and performance characteristics, demonstrating their superiority in comparison with manual systems.